Cost-Effectiveness Analysis Of Antidiabetic Medications In Patients With Type 2 Diabetes Mellitus At Rajawali Citra Hospital - Qarriy Aina Urfiyya; Nirma Nur Khasanah (Media Farmasi Indonesia, 2026)
Indonesia ranks fourth in the world for the number of individuals with diabetes mellitus (DM). To manage this growing health concern, it is crucial to implement treatments that include pharmacological therapies, such as antidiabetic. This study aims to identify the most cost-effective type of antidiabetic drug for patients with type 2 diabetes mellitus, based on the Average Cost-Effectiveness Ratio values. This study was a descriptive observational study that utilized medical records of outpatients with Type 2 Diabetes Mellitus at Rajawali Citra Hospital from 2023 to 2025, involving a total of 52 participants who met the criteria. The sampling technique employed was purposive sampling. Data analysis included demographic and clinical characteristics, factors influencing glycemic control, therapy cost components, and cost-effectiveness based on ACER values. The results indicated that the majority of diabetes patients were over the age of 45 (94.2%), with 67.3% being female. For BPJS patients, the most effective and cost-effective treatment was thiazolidinedione used as monotherapy, while the combination of metformin and acarbose proved to be the most effective. For the non-insured patients with type 2 diabetes, sulfonylurea was the most effective treatment as monotherapy, and the combination of sulfonylurea and acarbose was the most effective for combination therapy.